2012
DOI: 10.1007/s00227-011-1874-5
|View full text |Cite
|
Sign up to set email alerts
|

Do regular sea urchins show preference in which part of the body they orient forward in their walk?

Abstract: Regular sea urchins, which have pentaradial symmetry, have been believed to show no preference in which part of the body forward they proceed with. Through use of circular statistics, we show that the regular sea urchin Hemicentrotus pulcherrimus had no preference with respect to what body part, as determined by Lovén's system, should be anterior in locomotion. The sea urchins, however, preferably proceeded with the body part, which had contacted with the aquarium walls at rest, forward. When the contact part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…This may allow echinoderms to interact with the environment in all directions (Yoshimura et al 2012 ), although bilateral tendencies in locomotion are also reported . The major nerves are the circumoral nerve ring around the esophagus and the radial nerves along the ambulacra.…”
Section: Introduction the Echinoderm Body Planmentioning
confidence: 97%
“…This may allow echinoderms to interact with the environment in all directions (Yoshimura et al 2012 ), although bilateral tendencies in locomotion are also reported . The major nerves are the circumoral nerve ring around the esophagus and the radial nerves along the ambulacra.…”
Section: Introduction the Echinoderm Body Planmentioning
confidence: 97%
“…Jennings suggested that such a phenomenon, if found in a "higher animal", would be considered as a display of memory. Yoshimura and colleagues' work (Yoshimura et al, 2012(Yoshimura et al, , 2018, described in more detail later, amply confirm Jennings' observations in a species of sea urchins, but these 21 st -century works did not cite Jennings (1907).…”
Section: Learning In Echinodermsmentioning
confidence: 82%
“…Movement of starfish furnished another suggestion of associative learning (Jennings, 1907), a form of directional memory, as it was called a century later (Yoshimura et al, 2012;Yoshimura et al, 2018). A starfish that moves in a particular direction typically heads off again with the same leading arm after an interruption.…”
Section: Learning In Echinodermsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of them have focused on some regular echinoids and asteroids. Sea urchins appear to have no Anterior/Posterior axis of symmetry when crawling in an open space (Parker, 1936;Grabowsky, 1994;Yoshimura & Motokawa, 2008Yoshimura, Iketani, & Motokawa, 2012). Similarly, Preyer (1887, as cited in Cole, 1913) conducted some experiments with ophiuroids (Ophiomyxa sp.…”
Section: Discussionmentioning
confidence: 99%